2020
DOI: 10.1097/ftd.0000000000000710
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring Can Improve Linezolid Dosing Regimens in Current Clinical Practice: A Review of Linezolid Pharmacokinetics and Pharmacodynamics

Abstract: Linezolid is an antibiotic used to treat infections caused by drug-resistant gram-positive organisms, including vancomycin-resistant Enterococcus faecium, multi-drug resistant Streptococcus pneumoniae, and methicillin-resistant Staphylococcus aureus. The adverse effects of linezolid can include thrombocytopenia and neuropathy, which are more prevalent with higher exposures and longer treatment durations. Although linezolid is traditionally administered at a standard 600 mg dose every 12 hours, the resulting ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 80 publications
0
87
0
Order By: Relevance
“…Observational studies have suggested that the risk of myelosuppression is not only time dependent but also considerably higher in patients with renal impairment (4,5). However, limited data are available to determine the influence of kidney function on the pharmacokinetics of linezolid and its primary metabolites to support future therapeutic drug-monitoring (TDM) strategies targeted to reduce the risk of toxicity (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies have suggested that the risk of myelosuppression is not only time dependent but also considerably higher in patients with renal impairment (4,5). However, limited data are available to determine the influence of kidney function on the pharmacokinetics of linezolid and its primary metabolites to support future therapeutic drug-monitoring (TDM) strategies targeted to reduce the risk of toxicity (6).…”
mentioning
confidence: 99%
“…Standard curves were linear (r 2 Ն 0.99) for linezolid concentrations within 0.1 to 50 mg/liter and for concentrations of both metabolites within 0.1 to 25 mg/liter. Although concentrations should be reported in molar units, we report the concentrations of each analyte in the current work to permit direct comparison with prior literature (3,(6)(7)(8). The serum concentrations of linezolid and its two primary metabolites are provided in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These can include the critically ill, those with renal dysfunction, those with obesity, pediatric patients, and patients receiving p-glycoprotein (P-gp) modulators (rifampin). 35,36…”
Section: Linezolid In Perspectivementioning
confidence: 99%
“…These can include the critically ill, those with renal dysfunction, those with obesity, pediatric patients, and patients receiving p-glycoprotein (P-gp) modulators (rifampin). 35,36 Serum trough concentrations (C min ) between 2 and 8 ng/ mL, with a peak concentration of 10 to 20 ng/mL, have been suggested as normal for linezolid. 33,37 Some evidence has failed to find a correlation between abnormal levels and adverse clinical outcomes.…”
Section: Linezolid In Perspectivementioning
confidence: 99%